2018
DOI: 10.1007/s00426-018-0986-7
|View full text |Cite
|
Sign up to set email alerts
|

Rumination impairs the control of stimulus-induced retrieval of irrelevant information, but not attention, control, or response selection in general

Abstract: The aim of the study was to throw more light on the relationship between rumination and cognitive-control processes. Seventy-eight adults were assessed with respect to rumination tendencies by means of the LEIDS-r before performing a Stroop task, an event-file task assessing the automatic retrieval of irrelevant information, an attentional set-shifting task, and the Attentional Network Task, which provided scores for alerting, orienting, and executive control functioning. The size of the Stroop effect and irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Indeed, a negative association between rumination and inhibition has been shown in several clinical and experimental studies (Berman et al, 2011;Fawcett et al, 2015;Mor and Daches, 2015), although the research here is somewhat inconsistent, as at least four types of inhibition have been associated with rumination (viz. inhibition of distracting information, inhibition of no longer relevant information, proponent response inhibition and task switching inhibition; De Colzato et al, 2018;Owens and Derakshan, 2013;Whitmer and Banich, 2007;Zetsche et al, 2012). Despite this disparity between our findings and those within the clinical literature, our findings are broadly in line with those of Yang et al (2017), whose meta-analytic review reported significant associations between rumination and the functions of inhibition and shift.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, a negative association between rumination and inhibition has been shown in several clinical and experimental studies (Berman et al, 2011;Fawcett et al, 2015;Mor and Daches, 2015), although the research here is somewhat inconsistent, as at least four types of inhibition have been associated with rumination (viz. inhibition of distracting information, inhibition of no longer relevant information, proponent response inhibition and task switching inhibition; De Colzato et al, 2018;Owens and Derakshan, 2013;Whitmer and Banich, 2007;Zetsche et al, 2012). Despite this disparity between our findings and those within the clinical literature, our findings are broadly in line with those of Yang et al (2017), whose meta-analytic review reported significant associations between rumination and the functions of inhibition and shift.…”
Section: Discussionsupporting
confidence: 49%
“…Specifically, deficits in switching between internal representations in WM (e.g., Beckwé et al, 2014), in inhibiting previously relevant information (e.g., Whitmer & Banich, 2007) and in updating information in WM (e.g., Joormann & Gotlib, 2008) have all been related to trait rumination in dysphoric and non-dysphoric individuals as well as in individuals with major depressive disorder, after controlling for depressive tendencies. However, other studies have failed to find clear associations between impairments in cognitive control performance and rumination in similar samples (e.g., Alderman et al, 2015;Colzato, Steenbergen, & Hommel, 2018), or have even found enhanced cognitive control abilities to be associated with a higher tendency to ruminate (e.g., Altamirano, Miyake, & Whitmer, 2010;Zetsche & Joormann, 2011). For instance, Altamirano and colleagues (2010) observed that an enhanced ability to ignore the irrelevant dimensions of a stimulus was related to higher levels of trait rumination in dysphoric and non-dysphoric individuals.…”
Section: Introductionmentioning
confidence: 93%
“…However, other studies did not observe a relationship between increased reactive control (as reflected in performance enhancements) and increased levels of trait rumination in dysphoric and nondysphoric individuals as well as in individuals with major depressive disorder (Alderman et al, 2015;Colzato et al, 2018). For example, Colzato et al (2018) found that in dysphoric and non-dysphoric individuals, the size of the Stroop effect, suggesting increased reactive control, was positively related to the tendency to ruminate. However, controlling for levels of depression eliminated this significant relationship between increased reactive control and trait rumination.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, SM may support the ability to retrieve information consistent with prior knowledge or experience. Higher AC may enable the tendency of higher SM individuals to do so by facilitating the identification of retrieval cues consistent with prior knowledge or experience (Colzato, Steenbergen, & Hommel, 2018;Hills, Todd, & Goldstone, 2010;Liesefeld, Hoffmann, & Wentura, 2015;Lilienthal, Rose, Tamez, Myerson, & Hale, 2015;Schilling, Storm, & Anderson, 2014;Unsworth, Brewer, & Spillers, 2013). Therefore, it was hypothesized that SM would be negatively related to breaking mental set, but only for individuals with higher AC.…”
Section: Discussionmentioning
confidence: 99%